Ovulation Statuses of Surrogate Gilts Are Associated with the Efficiency of Excellent Pig Cloning - Huan, Yanjun (PLoS One, 2015)
Somatic cell nuclear transfer (SCNT) is an assisted reproductive technique that can produce multiple copies of excellent livestock. However, low cloning efficiency limits the application of SCNT. In this study, we systematically investigated the major influencing factors related to the overall cloning efficiency in pigs. Here, 13620 cloned embryos derived from excellent pigs were transferred into 79 surrogate gilts, and 119 live cloned piglets were eventually generated. During cloning, group of cloned embryos derived from excellent Landrace or Large white pigs presented no significant differences of cleavage and blastocyst rates, blastocyst cell numbers, surrogate pregnancy and delivery rates, average numbers of piglets born and alive and cloning efficiencies, and group of 101–150, 151–200 or 201–250 cloned embryos transferred per surrogate also displayed a similar developmental efficiency. When estrus stage of surrogate gilts was compared, group of embryo transfer on Day 2 of estrus showed significantly higher pregnancy rate, delivery rate, average number of piglets born, average alive piglet number or cloning efficiency than group on Day 1, Day 3, Day 4 or Day 5, respectively (P<0.05). And, in comparison with the preovulation and postovulation groups, group of surrogate gilts during periovulation displayed a significantly higher overall cloning efficiency (P<0.05). Further investigation of surrogate estrus stage and ovulation status displayed that ovulation status was the real factor underlying estrus stage to determine the overall cloning efficiency. And more, follicle puncture for preovulation, not transfer position shallowed for preovulation or deepened for postovulation, significantly improved the average number of piglets alive and cloning efficiency (P<0.05). In conclusion, our results demonstrated that ovulation status of surrogate gilts was the fundamental factor determining the overall cloning efficiency of excellent pigs, and follicle puncture, not transfer position change, improved cloning efficiency. This work would have important implications in preserving and breeding excellent livestock and improving the overall cloning efficiency.